α-Conotoxin TxIB Improved Behavioral Abnormality and Changed Gene Expression in Zebrafish (Danio rerio) Induced by Alcohol Withdrawal - Mao, Kailin; Li, Xiaodan; Chen, Zongde; Dong, Xiaoqian; Zhangsun, Dongting; Zhu, Xiaopeng; Luo, Sulan (Frontiers in Pharmacology, 2022)
Background and Purpose: Alcohol use disorder (AUD) is a serious public health issue and affects the lives of numerous people. Previous studies have shown a link between nicotinic acetylcholine receptors (nAChR) and alcohol addiction. However, the role of α6β2* nAChR in alcohol addiction remains obscure, and whether α6β2* nAChR can be used as a potential drug target for alcohol withdrawal need to be studied. Methods: Zebrafish (Danio rerio) were exposed to 0.2% alcohol for 14 days followed by 7 days of repeated withdrawal and then retro-orbitally injected with α-conotoxin TxIB (a selective α6β2* nAChR antagonist). Open Field Test was applied to characterize zebrafish behavior parameters. The monoamine neurotransmitter amounts and their mRNA expression in the zebrafish brain were identified using ELISA and quantitative real-time PCR (RT-PCR). RNA-sequencing (RNA-seq) and subsequent bioinformatics analysis were employed to explore the potential network regulation of TxIB after alcohol withdrawal. Results: The max speed in the center area of the Open Field Test was significantly higher in the withdrawal group whereas TxIB injection corrected this abnormality. The amount and mRNA expression of monoamine neurotransmitters did not change significantly after alcohol withdrawal and TxIB administration. RNA sequencing of zebrafish brain indicated a total of 657 genes showed aberrant expression and among which 225 were reversed after TxIB injection. These reversed genes were significantly enriched in the calcium ion binding pathway and the gene expression profile was further validated by RT-PCR. Conclusion: Our finding suggests α-conotoxin TxIB improved behavioral abnormality induced by alcohol-withdrawal, and changed gene expression mainly in the calcium signaling pathway. Therefore, α-conotoxin TxIB is expected to become a potential therapeutic agent for alcohol withdrawal.